Enhancing task specific ionic liquids' thermal stability by structural modification. - Schulz, Peter; Bösmann, Andreas; Wasserscheid, Peter (Monatshefte für Chemie, 2007)
Thermal retro-Michael decompn. of task specific ionic liqs. (TSILs) was efficiently suppressed by hydrogenation of the oxobutyl side chain yielding a hydroxy-functionalized TSIL. [on SciFinder(R)]
Keywords: task specific ionic liq thermal decompn suppression hydrogenation